Fracture Resistance, Surface Roughness, and Microtensile Bond Strength of Monolithic Zirconia to Resin Cements after Plasma Treatment - Mahsa Vafaei; Homayoon Alaghemand; Ghazaleh Ahmadizenous; Farshad Sohbatzadeh; Faraneh Mokhtarpour (Frontiers in Dentistry)
Objectives: This study aimed to assess the effect of surface treatment with plasma on surface roughness (SR) and fracture resistance (FR) of monolithic zirconia, and its microtensile bond strength (MTBS) to resin cements.